Beyond Acceptance and Resistance: Entrepreneurial Change Agency Responses in Policy Implementation. (7th August 2013) - McDermott, Aoife M.; Fitzgerald, Louise; Buchanan, David A.
Abstract : In this paper we explore how the implementation of public policy can differ from that mandated, and we argue that such departures are not necessarily a problem. Organizational change faces theoretical tension between considering non‐acceptance behaviours as 'resistance' and requiring change recipients to tailor and adapt change agendas to fit local contexts. This tension is particularly salient in the public sector, due to the mandated nature of much public reform. We compare the implementation of policy change in four hospital case studies in two countries (Ireland and the UK). Based on interviews with 68 staff across the four cases, we identify how change recipients can react to, translate and contribute to policy change initiatives. Our findings challenge a straightforward distinction between change agents and change recipients, showing how 'first‐order' recipients can act as 'second‐order' change agents. Entrepreneurial second‐order change agents use locally contextualized change agency to tailor and embellish policy mandates. We distinguish between 'adaptors', who make appropriate local adjustments, and 'extrapreneurs' who add extra dimensions to mandated change. This evidence suggests replacing the traditional 'acceptance–resistance' dichotomy with a continuum of responses to mandated policy, identifying how public sector actors can variously avoid, abstain, adopt, adapt or add to change agendas.